The role of Vitamin E – Selenium - Folic Acid Supplementation in Improving Sperm Parameters After Varicocelectomy: A Randomized Clinical Trial - Ardestani Zadeh, Arash; Arab, Davood; Kia, Naim Sadat; Heshmati, Sajjad; Amirkhalili, Seyed Nilofar (Urology Journal, 2019)
Purpose: In this study, we aimed to evaluate the effects of antioxidants including Vitamin E-Selenium-Folic acid (Vit E -Se- FA) on semen parameters following varicocelectomy (VCT). Materials and Methods: Sixty patients from 64 infertile male patients diagnosed with varicocele (VC) who underwent sub-inguinal VCT were included in the study. Following sub-inguinal VCT, the patients were randomized into two groups: 30 receiving Vit E-Se-FA supplementation for six months, and 30 as the control group with supplemental treatment. The post-operative semen parameters of Vit E-Se-FA receiving group were compared with control group at the end of experiment. The sperm count, percentage of motile and abnormal sperms were considered. Results: There were statistically significant differences in terms of count (P = .031) and motility (P = .01) of sperm after six months of receiving Vit E-Se-FA supplementation comparing with control group. Conclusion: Vit E-Se-FA supplementation can improve sperm parameters (count and motility of sperm) after VCT.